2015
DOI: 10.3389/fpsyg.2015.01801
|View full text |Cite
|
Sign up to set email alerts
|

Syllable Structure Universals and Native Language Interference in Second Language Perception and Production: Positional Asymmetry and Perceptual Links to Accentedness

Abstract: The present study investigated how syllable structure differences between the first Language (L1) and the second language (L2) affect L2 consonant perception and production at syllable-initial and syllable-final positions. The participants were Mandarin-speaking college students who studied English as a second language. Monosyllabic English words were used in the perception test. Production was recorded from each Chinese subject and rated for accentedness by two native speakers of English. Consistent with prev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 109 publications
0
10
0
Order By: Relevance
“…In contrast, English is a canonical stress-timed language, and Mandarin is characterized as syllable-timed (e.g., Grabe & Low, 2002). In addition, L1-L2 differences in syllable structure have been shown to affect L2 speech learning (Cheng & Zhang, 2015). The difference in unit structure, mora for Japanese and syllable for English and Mandarin, relates to differential durational implementation.…”
Section: Japanese As the Target L2mentioning
confidence: 99%
“…In contrast, English is a canonical stress-timed language, and Mandarin is characterized as syllable-timed (e.g., Grabe & Low, 2002). In addition, L1-L2 differences in syllable structure have been shown to affect L2 speech learning (Cheng & Zhang, 2015). The difference in unit structure, mora for Japanese and syllable for English and Mandarin, relates to differential durational implementation.…”
Section: Japanese As the Target L2mentioning
confidence: 99%
“…When this transfer is negative, it is referred to as interference. One example of interference is when pronunciation or vocabulary knowledge from a previous language interferes with new pronounciation (see Cheng & Zhang, 2015, for a recent discussion and investigation). An example of positive transfer is when learning a foreign language's vocabulary supports a deeper understanding of one's native language vocabulary (e.g., Cunningham & Graham, 2000); this principle extends to the development of reading skills (Gebauer, Zaunbauer, & Möller, 2013) in both directions, but strongest from foreign to native language reading fluency and comprehension.…”
Section: Japanese Education and Language Learningmentioning
confidence: 99%
“…In dyslexia research, a subgroup of children was found to be linked with a potential deficit in neural discriminatory sensitivity to envelope changes in speech and nonspeech sounds [ 104 ]. In a cross-language study, language experience has been shown to play an important role in differentially coding speech sounds in onset and offset positions [ 105 ]. Future clinical work and cross-language neurophysiological studies can further test the reliability and diagnostic utility of distinct ON and OFF responses to time-varying sounds with rising versus falling intensity and how they are affected by linguistic experience or pathological conditions.…”
Section: Discussionmentioning
confidence: 99%